(untitled) (Research, Society and Development, 2020)
Objective: Perform a comparative analysis of error measurements after training with virtual and real darts. Methodology: The study included 15 stroke patients (10 men) and 12 healthy individuals (7 men). The virtual game used was Kinect Sports on the Xbox 360 Kinect®. Participants made 15 attempts at each game. Absolute (AE), constant (CE) and variable (VE) errors were calculated. Data analysis was performed using ANOVA. Results: A significant difference was observed between patients and healthy people in the virtual game (p = 0.003) and in the real game (p = 0.0001) for AE. There was difference in AE between virtual and real games for patients (p = 0.0001). In the EC, no significant difference was found between patients and healthy in the virtual game (p = 0.355) and in the real game (p = 0.544). There was also no difference in EC between virtual and real games for patients (p = 0.452). Through the analysis of the EV, there was no significant difference between patients and healthy people in the virtual game (p = 0.406), but there was in the real game (p = 0.0001). There was no significant difference in EV between virtual and real games for patients (p = 0.579). Conclusion: The results found indicated that the patients had less precision, greater consistency of errors and less variability in performance. The virtual game provided better results for patients compared to the real game, which can be of significant importance for the planning of motor rehabilitation of stroke patients.